Ukrainian Higher Education Law: Key Highlights and Relationships with Lithuanian Science and Study Policy - Shapoval, Roman Volodymyrovych; Matulienė, Snieguolė; Juodkaitė-Granskienė, Gabrielė (Pedagogika, 2016)
The article provides an overview of the Ukrainian Law on Higher Education – defined innovations, establishing a higher education organization, financing and quality assurance principles for the development of competitive human capital guidelines. The article compares these aspects between two countries, Lithuania and Ukraine, emphasizing research and studies in the sphere, giving some insight on these systems. Also authors discusses possible improvements, according to the two states existing best practices in higher education in different areas of Strategy.